2010
DOI: 10.1007/s11307-010-0316-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cellular Proliferation in Rat Skeletal Muscle and Tendon in Response to Exercise: Use of FLT and PET/CT

Abstract: FLT-PET seems to be a promising tool for imaging of exercise-induced cellular proliferation in musculo-tendinous tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The exercise protocol in the present study was similar to an earlier study where PET and the tracer 3′-deoxy-3′-[ 18 F]fluoro-thymidine (FLT) were used for detecting an increased cellular proliferation in Achilles tendon and skeletal muscle [39] . Therefore, a parallel increased production of extracellular matrix proteins like the collagens was obviously expected as part of the adaptation process.…”
Section: Discussionmentioning
confidence: 99%
“…The exercise protocol in the present study was similar to an earlier study where PET and the tracer 3′-deoxy-3′-[ 18 F]fluoro-thymidine (FLT) were used for detecting an increased cellular proliferation in Achilles tendon and skeletal muscle [39] . Therefore, a parallel increased production of extracellular matrix proteins like the collagens was obviously expected as part of the adaptation process.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that treadmill running enhances mouse patellar and Achilles tendon stem/progenitor cell proliferation and increases collagen production (70% and 200% respectively) (33). Enhanced cellular proliferation in rat skeletal muscle and tendon was reported by Skovgaard et al (42) as a result of only 3 d of endurance training. Furthermore, repeated stretching exercises of rat calcaneal tendon (10 repetitions three or five times a week for 21 d) induced cellularity and collagen increase, and about twice the amount of glycosaminoglycan synthesis (43).…”
Section: Introductionmentioning
confidence: 90%
“…In addition to the functional aspect of scintigraphy, PET offers additional advantages such as cross‐sectional imaging, higher sensitivity, and spatial resolution, and the availability of a variety of tracers . In particular, the use of 18 F‐FDG PET could improve detection of inflammation compared to using radiolabeled white blood cells, and could also improve investigation of tendinopathy/desmopathy in the horse …”
Section: Introductionmentioning
confidence: 99%